Single-step noncompetitive immunocomplex immunoassay for rapid aflatoxin detection - Peltomaa Riikka; Abbas Asmaa; Yli-Mattila Tapani; Lamminmäki Urpo (Elsevier Ltd, 2022)
Owing to the high carcinogenicity of aflatoxins, these toxic secondary metabolites pose a severe risk to human and animal health and can have major economic implications. Herein, we report the development of a noncompetitive immunoassay for aflatoxins based on a monoclonal capture antibody and a unique anti-immunocomplex (anti-IC) antibody fragment (scFv) isolated from a synthetic antibody repertoire. The anti-IC scFv recognizes the immunocomplex and enables the development of noncompetitive sandwich-type assays despite the small size of the analyte. The single-step assay developed in this work, with a detection limit of 70 pg mL−1, could detect aflatoxins within 15 min. The assay was applied to the analysis of spiked food samples, and the results showed that the method could provide a rapid and simple tool for aflatoxin detection. Moreover, the work demonstrates the potential of anti-IC antibodies and non-competitive immunoassays for the analysis of small molecule contaminants.